Ephemeral Coast, S. Wales - Jeffery, Celina (punctum books, 2014)
Ephemeral Coast is a curatorial research project that seeks to investigate our difficult relationship to the coast as a threshold and frontline to climate change and considers the possibilities of understanding art in relation to what may be described as an unparalleled event. Ephemeral Coast involves the curation of exhibitions, located in coastal regions of the US/Canadian Arctic, Wales, and Mauritius and is made up primarily of artists, cultural theorists and climate change scientists. This catalogue is a theoretical extension of the artists' work presented in first installment of the exhibition in south Wales, UK. The catalogue discusses the curatorial process and incorporates essays by guest authors, who re-contextualize Ephemeral Coast, S Wales within discussions of regional climate change and cultural theory.